Edaphic Diversity, Polychemical Soil Status of the Prinevskaya Lowland and Prospects for Soils Use - Ekaterina Yu. Chebykina; Timur I. Nizamutdinov; Evgeny V. Abakumov; Natalia V. Dinkelaker (Land)
There will be a significant increase in anthropogenic load on the soils of the Prinevskaya lowland in the nearest decade due to the fact that a significant territory is occupied by St. Petersburg. The main objective is a study of the sanitary-hygienic state and soil diversity of the Prinevskaya lowland in case of a high degree of agricultural soil development there and the significant role of the lithological factor. Soils were studied at the following land use and land cover: agricultural and fallow soils of agrolandscapes; forest soils; and soils of industrial areas. Studies were carried out using morphological descriptions and analyses of chemical, physical, and biological properties. The most vulnerable land use are forest and agricultural and fallow zones, where active accumulation of priority toxicants of anthropogenic origin can occur. Geochemical peculiarities of studied soils are deficit of Mn, Cu, Mo, and Zn in soil-forming rock materials and accumulation of strontium and lead in arable horizons. The soils examined show minimal contamination with trace elements, as verified by a range of individual and combined ecotoxicological indicators. Urban development planning, particularly in St. Petersburg, should prioritize the preservation of biodiversity and soil resources.